Fasciola hepatica-Derived Molecules as Regulators of the Host Immune Response - Ryan, Sinéad; Shiels, Jenna; Taggart, Clifford C.; Dalton, John P.; Weldon, Sinéad (Frontiers in Immunology, 2020)
Helminths (worms) are one of the most successful organisms in nature given their ability to infect millions of humans and animals worldwide. Their success can be attributed to their ability to modulate the host immune response for their own benefit by releasing excretory-secretory (ES) products. Accordingly, ES products have been lauded as a potential source of biotherapeutics for an array of inflammatory diseases. However, there is a significant lack of knowledge regarding the specific interactions between these products and cells of the immune response. Many different compounds have been identified within the helminth ‘secretome’, each with unique influences on the host inflammatory response. Helminth defence molecules (HDMs) are a conserved group of proteins initially discovered in the secretome of the liver fluke, Fasciola hepatica. HDMs interact with cell membranes without cytotoxic effects and do not exert antimicrobial activity, suggesting that these peptides evolved specifically for immunomodulatory purposes. A peptide generated from the HDM sequence, termed FhHDM-1, has shown extensive anti-inflammatory abilities in clinically relevant models of a range of diseases, offering hope for the development of a new class of therapeutics, and mechanism(s) by which FhHDM-1 modulates the host immune system continue to be discovered. In this review, the current knowledge of host immunomodulation by FhHDM-1 will be discussed and its potential exploitation as a novel therapeutic will be explored. Immunomodulatory products, including HDMs, have been identified from other helminths and their effects will also be outlined to broaden our understanding of the variety of effects these potent molecules exert.